UNIFORM BOUNDARY STABILIZATION OF QUASILINEAR WAVE EQUATION WITH NONLINEAR BOUNDARY DAMPING AND SOURCE TERM - Cabanillas Lapa, Eugenio (2010)
In this work we are concerned with the existence of strong solutions andexponential decay of the total energy for the initial boundary value problem associatedwith the quasilinear wave equation with nonlinear source, under the assumption thatthe velocity boundary feedback is dissipative. The results are proved by means ofthe potential well method, the multiplier technique and suitable unique continuationtheorem for the wave equation with variable coefficients.